The Use of KineMaster Video Media in Learning Maharatul Kalam for Grade IX Students at Al-Azhar 32 Islamic Junior High School Padang - Sri Jomila Oktari; Muhammad Fadhil Hadziq; Bulqis (Program Studi Pendidikan Bahasa Arab, 2026)
This study aims to analyze the use of KineMaster video media in the teaching of maharatul kalam (Arabic speaking skills) among ninth-grade students at SMP Islam Al-Azhar 32 Padang. The background of the research is the low interest and speaking ability of students due to conventional, monotonous teaching methods and a lack of innovative media. The study employs Classroom Action Research (CAR) with a descriptive qualitative approach. The research subjects were 20 ninth-grade students, and data were collected through observation, interviews, questionnaires, documentation, and speaking skill tests. The results show that the use of KineMaster video media can improve students’ learning motivation, fluency of pronunciation (lahjah), and learning independence. As many as 80% of students felt motivated to learn, 70% demonstrated fluency in pronunciation, and 65% were able to learn independently using video media. KineMaster video media also made learning more interactive, creative, and enjoyable. However, some technical challenges were found in the creation and utilization of video media, indicating the need for teacher training and school facility support. Overall, KineMaster video media is effective in enhancing students’ maharatul kalam skills and can be an innovative solution for Arabic language learning in the digital era. This study recommends the continuous integration of digital media in the learning process.